Ultrafine diamond compact and manufacturing method thereof

By optimizing the preparation process of ultrafine diamond composite sheets, including mechanical stirring, ultrasonic dispersion, high-temperature and high-pressure sintering and laser densification treatment, the problems of uneven particle distribution and insufficient interface binding force are solved, and the hardness, wear resistance and impact resistance of the composite sheets are significantly improved.

CN119657928APending Publication Date: 2025-03-21JINHUA ZHONGYE SUPERHARD MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411719759.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

During the preparation process, existing ultrafine diamond composite sheets have uneven particle distribution and insufficient interface binding force, resulting in unstable surface hardness and wear resistance.

Method used

By selecting high-purity diamond powder with particle size of 0.1μm-1μm and cobalt-based alloy and nano-scale ceramic particles as materials, mechanical stirring, ultrasonic dispersion and high-temperature and high-pressure sintering technology are used to enhance the bonding strength of diamond particles and matrix.

Benefits of technology

It significantly improves the distribution uniformity and interface bonding force of diamond particles in the matrix, improves the hardness, wear resistance and impact resistance of the composite sheet, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657928A_ABST
    Figure CN119657928A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of superhard composite materials, in particular to a manufacturing method of a superfine diamond compact, which is characterized by comprising the following steps: S1, raw material selection and pretreatment: diamond particles: selecting high-purity diamond powder with the particle size of 0.1-1 mu m; a hard alloy, such as a cobalt-based alloy, is adopted as a matrix material; nanoscale ceramic particles such as silicon nitride and aluminum oxide are added to serve as the reinforcing materials, gaps between the base body and the diamond particles are filled, and the compactness of the materials is improved; and S2, diamond particle uniform distribution treatment is conducted, specifically, a mechanical stirring and ultrasonic dispersion combined method is adopted, the diamond particles and the matrix powder are fully mixed, the matrix powder and the diamond particles are stirred at a low speed through mechanical stirring, and the particles are preliminarily dispersed. And the uniformity is improved: mechanical stirring, ultrasonic dispersion and electrostatic dispersion are combined, so that the distribution uniformity of diamond particles in a matrix is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of superhard composite materials, and in particular to an ultrafine diamond composite sheet and a manufacturing method thereof. Background Art

[0002] Diamond composite sheet, also known as diamond and cemented carbide composite material, is synthesized by diamond micropowder and cemented carbide substrate under high temperature and high pressure. This material has the hardness and wear resistance of diamond, and has superior impact resistance due to the presence of cemented carbide substrate. It is an excellent composite material. It is widely used in the manufacture of oil drill bits, geological drill bits and cutting tools. The grain size of diamond in diamond composite sheet has an important influence on product performance. The smaller the grain, the better the impact toughness. At the same time, it can have both hardness and wear resistance, which is particularly suitable for precision / ultra-precision processing of materials. For example, diamond polycrystals with a grain size of less than 1μm and uniform microstructure have excellent performance when used as cutting tools or wire drawing dies;

[0003] However, the ultrafine diamond composite sheets in the prior art have the following problems during the preparation process:

[0004] 1. Uneven distribution of particles: In traditional methods, diamond particles are often unevenly distributed, resulting in unstable surface hardness and wear resistance of the composite sheet.

[0005] 2. Insufficient interface bonding strength: During the traditional high temperature and high pressure sintering process, the bonding strength between diamond particles and the matrix is ​​weak, which is prone to peeling and affects impact resistance.

[0006] Therefore, an ultrafine diamond composite sheet and a manufacturing method thereof are proposed. Summary of the invention

[0007] The purpose of the present invention is to provide an ultrafine diamond composite sheet and a method for making the same, which can improve the hardness, wear resistance and bonding strength of the composite sheet by improving the distribution of diamond particles, optimizing the sintering process and adding composite reinforcement materials, so as to solve the problems raised in the above background technology.

[0008] To achieve the above object, the present invention provides the following technical solution: a method for making an ultrafine diamond composite sheet, characterized in that it comprises the following steps:

[0009] S1. Raw material selection and pretreatment:

[0010] Diamond particles: Select high-purity diamond powder with a particle size of 0.1μm-1μm;

[0011] Matrix material: Use cemented carbide, such as cobalt-based alloy as the matrix;

[0012] Reinforcement materials: Add nano-scale ceramic particles, such as silicon nitride and alumina, as reinforcement materials to fill the gaps between the matrix and diamond particles and increase the density of the material;

[0013] S2. Diamond particles are evenly distributed by combining mechanical stirring with ultrasonic dispersion to fully mix the diamond particles and the matrix powder, wherein mechanical stirring is used to stir the matrix powder and the diamond particles at a low speed to preliminarily disperse the particles, and ultrasonic dispersion is used for 1-2 hours to make the particles more evenly dispersed;

[0014] S3, high temperature sintering, using high temperature and high pressure sintering technology. The sintering conditions are pressure of 6GPa-8GPa, temperature of 1400℃-1500℃, and sintering time is controlled within 30 minutes. A diffusion model is built in the sintering process. The relationship between sintering temperature, pressure and sintering time is calculated through the diffusion model to obtain the best bonding strength.

[0015] The diffusion model formula is:

[0016]

[0017] Where: D is the diffusion coefficient, D0 is the pre-factor, Q is the activation energy, R is the gas constant, T is the sintering temperature, and by adjusting the temperature T and pressure parameters, which control the diffusion rate of the matrix material and affect the bonding strength between particles;

[0018] S4, surface densification treatment. After sintering, the surface of the composite sheet is subjected to laser densification treatment. The laser parameters are controlled to have a power density of 10^6-10^7 W / cm 2 The processing time is 3 minutes to 5 minutes.

[0019] Preferably, in the step S3, high temperature sintering, a graded sintering strategy is also adopted, and the graded sintering strategy includes a three-stage temperature increase strategy, so that the diamond particles and the matrix material can gradually achieve stable bonding in a mild temperature gradient;

[0020] The first stage: the temperature is initially raised to 1400°C and kept at this temperature for 5 minutes. The temperature is lower than the graphitization point, so that the matrix powder particles are slightly fused, the density of the material is improved, and a stable base is provided for subsequent heating.

[0021] The second stage: further heating to 1450°C, holding time 10 minutes, this stage improves the bonding effect between diamond particles and matrix materials, while controlling the temperature below the critical point of graphitization;

[0022] The third stage: the temperature is raised to 1500°C and kept at this temperature for 3 minutes to ensure complete sintering of the matrix. At the same time, low temperature and high pressure are used to prevent surface oxidation of the particles and graphitization of the interface.

[0023] Preferably, the graded sintering strategy also includes optimizing the heating path and adopting a nonlinear heating curve, so that the heating rate is faster in the low temperature section and gradually slows down in the high temperature section, thereby reducing the thermal stress between particles;

[0024] Nonlinear temperature rise formula:

[0025]

[0026] Where: T(t) is the temperature at time t, T init is the starting temperature, T final is the target temperature, t total is the total heating time, α is the heating rate control index, and a value greater than 1 can slow down the heating rate in the high temperature section.

[0027] Preferably, the heating path optimization also includes controlling the heating rate, and controlling the heating rate includes temperature and diffusion rate control and heating rate adaptive control;

[0028] The diffusion rate formula is:

[0029]

[0030] Where: D is the diffusion coefficient, D0 is the diffusion pre-factor, Q is the activation energy of diffusion, R is the gas constant, and T is the current temperature;

[0031] The temperature rise rate is adaptively controlled, and the temperature change during the sintering process is fed back in real time through the temperature sensor and the control system, and the temperature rise rate is adjusted in real time using an adaptive control algorithm to maintain the stability of the temperature change;

[0032] Adaptive control formula:

[0033] S rate (t+1)=S rate (t)-η(T actual -T target )

[0034] Where: S rate (t+1) is the heating rate at the next moment, η is the adjustment coefficient, T actual is the current actual temperature, T target is the target temperature.

[0035] Preferably, the three-stage heating strategy in the graded sintering strategy introduces multiple insulation stages to set insulation intervals at different temperature stages during the heating process, so that the heat distribution in the material is uniform;

[0036] Maintain constant temperature at the target temperature point in each stage to allow the matrix and diamond particles to fully diffuse and fuse. Insulation stage formula T hold= constant, maintain constant temperature T during the insulation time hold , ensuring that the material is heated evenly;

[0037] In graded sintering, the holding time is extended to promote the migration distance of diamond particles to reach the optimal value. The optimal holding time can be determined by calculating the diffusion distance.

[0038] Diffusion distance formula:

[0039]

[0040] Where: L is the diffusion distance, D is the diffusion coefficient, t hold For the holding time, select the appropriate holding time t hold Make the diffusion distance L meet the requirements.

[0041] Preferably, the graded sintering further optimizes the graded sintering atmosphere, utilizes inert gas protection, introduces inert gas into the sintering environment, and ensures the stability of the diamond particles through the protective atmosphere formula;

[0042] Protective atmosphere control formula:

[0043]

[0044] Where: C inert is the inert gas concentration, V inert is the inflow of inert gas, V chamber The volume of the sintering furnace is maintained at a concentration of inert gas above 95% during the high temperature stage.

[0045] Preferably, the atmosphere pressure control is further introduced into the graded sintering atmosphere optimization to dynamically adjust the pressure of the sintering cavity according to different stages in the graded sintering;

[0046] Atmosphere pressure linkage formula:

[0047] P inert (t) = P0 + α·T(t)

[0048] Where: P inert (t) is the inert gas pressure, P0 is the initial pressure, T(t) is the temperature at time t, and α is the adjustment parameter.

[0049] Preferably, the surface densification step S4 adopts a multi-step laser scanning process;

[0050] The multi-step laser scanning process includes:

[0051] First scan: low-power rapid scan to preliminarily fill tiny pores on the surface;

[0052] Second scan: Scan slowly with moderate power to further eliminate surface micropores and improve density;

[0053] The third scan: high-power fine scanning to form a dense and smooth surface layer;

[0054] Laser power and scanning speed formula:

[0055] E input =P·t scan

[0056] Where: E input is the input energy, P is the laser power, t scan is the scanning time.

[0057] Preferably, the step S4, surface densification treatment, includes using argon plasma to pre-treat the surface before densification to remove surface oxides and activate the surface layer, and after laser densification treatment, nitrogen plasma passivation is performed to form a nitride layer on the surface;

[0058] Plasma activation formula:

[0059]

[0060] Where: D plasma is the diffusion coefficient after plasma treatment, E a is the activation energy, k is the Boltzmann constant, and T is the temperature.

[0061] An ultrafine diamond composite sheet includes the following proportions:

[0062] Ultrafine diamond particles: 50% to 70%, particle size: 0.1μm-1μm;

[0063] Cobalt-based alloy powder: 20% ~ 30%;

[0064] Reinforcement material: 5% to 10%;

[0065] Interface binder: 2% to 5%;

[0066] Dispersant: appropriate amount.

[0067] Compared with the prior art, the present invention has the following beneficial effects:

[0068] 1. Improved uniformity: The combination of mechanical stirring, ultrasonic dispersion and electrostatic dispersion significantly improves the distribution uniformity of diamond particles in the matrix.

[0069] 2. Enhanced interface bonding strength: The addition of interface binder and graded sintering technology effectively enhances the bonding strength between diamond particles and the matrix, avoiding peeling and falling off problems.

[0070] 3. Reduced graphitization tendency: The low-temperature and high-pressure sintering process is carried out under argon protection, which effectively reduces the graphitization tendency of diamond particles.

[0071] 4. Improved surface hardness and wear resistance: The combination of surface laser densification and plasma coating significantly improves the surface hardness and wear resistance of the composite sheet and extends its service life;

[0072] 5. Stability of particle structure: Through inert gas protection and graded temperature rise path, particle graphitization and interface degradation are avoided to maintain the high hardness of the material.

[0073] 6. Improved interface bonding strength: Multiple heat preservation strategies and adaptive heating rate control enhance the bonding strength between particles and effectively improve the impact resistance of the composite sheet.

[0074] 7. Improved densification effect: Introducing the heat preservation stage and optimizing the diffusion distance control to ensure that the internal structure of the composite sheet after sintering is dense and uniform, and improve the wear resistance of the composite sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0076] Figure 1 The present invention is a flow chart of the method for making the ultrafine diamond composite sheet;

[0077] Figure 2 The following is a parameter comparison table of the ultrafine diamond composite sheet formula of the present invention and the traditional ultrafine diamond composite sheet formula. DETAILED DESCRIPTION

[0078] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0079] See also Figure 1 to Figure 2 , the technical solution provided by the present invention:

[0080] Embodiment 1:

[0081] A method for manufacturing an ultrafine diamond composite sheet comprises the following steps:

[0082] S1. Raw material selection and pretreatment:

[0083] Diamond particles: Select high-purity diamond powder with a particle size of 0.1μm-1μm. Ultrafine diamond particles have high hardness and large specific surface area, which can effectively improve the surface hardness and wear resistance of the composite sheet;

[0084] Matrix material: Use cemented carbide, such as cobalt-based alloy, as the matrix to ensure that the composite sheet has good toughness and impact resistance;

[0085] Reinforcement materials: Add nano-scale ceramic particles, such as silicon nitride and alumina, as reinforcement materials to fill the gaps between the matrix and diamond particles and increase the density of the material;

[0086] S2. In order to ensure the uniform distribution of diamond particles in the matrix, the diamond particles are evenly distributed. A method combining mechanical stirring and ultrasonic dispersion is used to fully mix the diamond particles and the matrix powder to avoid particle aggregation and ensure the hardness and wear resistance of the composite sheet. The mechanical stirring stirs the matrix powder and the diamond particles at a low speed to preliminarily disperse the particles. The ultrasonic dispersion is used for 1-2 hours to make the particles more evenly dispersed.

[0087] S3. High temperature sintering. In order to reduce the graphitization tendency of diamond particles, high temperature and high pressure sintering technology is adopted. The sintering conditions are pressure of 6GPa-8GPa, temperature of 1400℃-1500℃, and sintering time is controlled within 30 minutes. A diffusion model is built in the sintering process. The relationship between sintering temperature, pressure and sintering time is calculated through the diffusion model to obtain the best bonding strength. Low temperature sintering can not only effectively protect the diamond particles, but also improve the bonding strength of the composite sheet.

[0088] The diffusion model formula is:

[0089]

[0090] Where: D is the diffusion coefficient, D0 is the pre-factor, Q is the activation energy, R is the gas constant, T is the sintering temperature, and by adjusting the temperature T and pressure parameters, which control the diffusion rate of the matrix material and affect the bonding strength between particles;

[0091] S4, surface densification treatment. After sintering, the surface of the composite sheet is subjected to laser densification treatment. The laser parameters are controlled to have a power density of 10^6-10^7 W / cm 2 The processing time is 3 minutes to 5 minutes. The hardness and wear resistance of the composite sheet are further improved. Laser processing can close the tiny pores on the surface and improve the density and smoothness of the material.

[0092] In the step S3, high temperature sintering, a graded sintering strategy is also adopted, which includes a three-stage temperature increase strategy, so that the diamond particles and the matrix material can be gradually and stably combined in a gentle temperature gradient;

[0093] The first stage: the temperature is initially raised to 1400°C and kept at this temperature for 5 minutes. The temperature is lower than the graphitization point, so that the matrix powder particles are slightly fused, the density of the material is improved, and a stable base is provided for subsequent heating.

[0094] The second stage: further heating to 1450°C, holding time 10 minutes, this stage improves the bonding effect between diamond particles and matrix materials, while controlling the temperature below the critical point of graphitization;

[0095] The third stage: the temperature is raised to 1500°C and kept at this temperature for 3 minutes to ensure complete sintering of the matrix. At the same time, low temperature and high pressure are used to prevent surface oxidation of the particles and graphitization of the interface.

[0096] The purpose of adopting the graded sintering strategy is to gradually increase the temperature and control the temperature change during the sintering process, so that the diamond particles and the matrix material can be gradually fused at a lower temperature to avoid the particle graphitization and interface peeling caused by high temperature. In order to further optimize the graded sintering strategy, improvements can be made in the following aspects: optimizing the heating path, controlling the heating rate, introducing the insulation stage, and determining the optimal temperature and time through precise calculation to ensure the high density and high strength of the diamond composite sheet:

[0097] The graded sintering strategy also includes optimizing the heating path and using a nonlinear heating curve so that the heating rate is faster in the low temperature section and gradually slows down in the high temperature section to reduce the thermal stress between particles;

[0098] Nonlinear temperature rise formula:

[0099]

[0100] Where: T(t) is the temperature at time t, T init is the starting temperature, T final is the target temperature, t total is the total heating time, α is the heating rate control index, and a value greater than 1 can slow down the heating rate in the high temperature section.

[0101] During the sintering process, the temperature will directly affect the diffusion rate of the matrix material. Controlling the diffusion rate can prevent the uneven bonding between particles caused by excessive temperature or the fragile interface caused by rapid diffusion. The heating path optimization also includes controlling the heating rate, which includes temperature and diffusion rate control and adaptive heating rate control.

[0102] The diffusion rate formula is:

[0103]

[0104] Where: D is the diffusion coefficient, D0 is the diffusion pre-factor, Q is the diffusion activation energy, R is the gas constant, and T is the current temperature. During the step-by-step heating process, the temperature is controlled in stages to keep the diffusion rate within an appropriate range to prevent excessive diffusion at high temperatures from causing poor bonding of particles in the composite material.

[0105] The temperature rise rate is adaptively controlled, and the temperature change during the sintering process is fed back in real time through the temperature sensor and the control system, and the temperature rise rate is adjusted in real time using an adaptive control algorithm to maintain the stability of the temperature change;

[0106] Adaptive control formula:

[0107] S rate (t+1)=S rate (t)-η(T actual -T target )

[0108] Where: S rate (t+1) is the heating rate at the next moment, η is the adjustment coefficient, T actual is the current actual temperature, T target To achieve the target temperature, the heating rate is adjusted through real-time feedback to ensure a smooth sintering process and reduce the risk of cracks caused by thermal stress.

[0109] In the process of heating, the heat preservation interval is set at different temperature stages to make the heat in the material evenly distributed and reduce the material defects caused by thermal stress. The three-stage heating strategy in the graded sintering strategy introduces multiple heat preservation stages to set the heat preservation interval at different temperature stages in the heating process to make the heat in the material evenly distributed.

[0110] Maintain constant temperature at the target temperature point in each stage to allow the matrix and diamond particles to fully diffuse and fuse. Insulation stage formula T hold = constant, maintain constant temperature T during the insulation time hold , ensuring that the material is heated evenly;

[0111] In graded sintering, appropriately extending the holding time can promote the migration distance of diamond particles to reach the optimal value. By calculating the diffusion distance, the optimal holding time can be determined;

[0112] Diffusion distance formula:

[0113]

[0114] Where: L is the diffusion distance, D is the diffusion coefficient, t hold For the holding time, select the appropriate holding time t holdEnsuring that the diffusion distance L meets the requirement is conducive to uniform densification of the interior of the material.

[0115] The graded sintering further optimizes the graded sintering atmosphere, utilizes inert gas protection, introduces inert gas into the sintering environment, and ensures the stability of the diamond particles through the protective atmosphere formula;

[0116] Protective atmosphere control formula:

[0117]

[0118] Where: C inert is the inert gas concentration, V inert is the inflow of inert gas, V chamber The volume of the sintering furnace is maintained at a concentration of inert gas above 95% during the high temperature stage.

[0119] The atmosphere pressure control is further introduced into the optimization of the graded sintering atmosphere, and the pressure of the sintering cavity is dynamically adjusted according to different stages in the graded sintering, so that the particles are more evenly distributed during the diffusion process;

[0120] Atmosphere pressure linkage formula:

[0121] P inert (t) = P0 + α·T(t)

[0122] Where: P inert (t) is the inert gas pressure, P0 is the initial pressure, T(t) is the temperature at time t, and α is the adjustment parameter.

[0123] The purpose of surface densification treatment is to improve the surface hardness, wear resistance and corrosion resistance of ultrafine diamond composite sheets. By optimizing laser densification, introducing plasma-assisted treatment, and composite coating technology, the surface density, smoothness and durability of the composite sheet can be effectively improved. The S4, surface densification treatment step adopts a multi-step laser scanning process;

[0124] The multi-step laser scanning process includes:

[0125] First scan: low-power rapid scan to preliminarily fill tiny pores on the surface;

[0126] Second scan: Scan slowly with moderate power to further eliminate surface micropores and improve density;

[0127] The third scan: high-power fine scanning to form a dense and smooth surface layer;

[0128] Laser power and scanning speed formula:

[0129] E input =P·t scan

[0130] Where: E input is the input energy, P is the laser power, t scan is the scan time.

[0131] Embodiment 2:

[0132] Pulsed laser densification: Using pulsed laser instead of continuous laser can precisely control the energy input of each pulse, making the densification process more uniform and reducing the risk of micro cracks on the surface caused by high heat;

[0133] Pulse laser formula: E pulse =P peak ·τ

[0134] Where: E pulse is the energy of a single pulse, P peak is the peak power, τ is the pulse duration, and in pulse laser mode, the energy of each pulse can be precisely set, so that the surface densification process proceeds stably and surface deformation and microcracks caused by heat accumulation are avoided;

[0135] Plasma-assisted treatment can further improve the surface density and corrosion resistance. By combining plasma treatment such as argon or nitrogen with laser densification, the durability of the composite surface can be enhanced.

[0136] The step S4, surface densification treatment, includes using argon plasma to pre-treat the surface before densification to remove surface oxides and activate the surface layer, and after laser densification treatment, nitrogen plasma passivation to form a nitride layer on the surface;

[0137] Plasma activation formula:

[0138]

[0139] Where: D plasma is the diffusion coefficient after plasma treatment, E a is the activation energy, k is the Boltzmann constant, and T is the temperature. The plasma activation energy increases the surface energy of the diamond particles, making it easier to form a dense bonding layer during the laser densification process, thereby increasing the wear resistance of the material.

[0140] Nitrogen plasma passivation: After laser densification treatment, nitrogen plasma passivation is performed to form a nitride layer on the surface, thereby improving the oxidation resistance and corrosion resistance of the composite sheet. The nitridation reaction formula is: N2+2e - →2N - , the active nitrogen atoms in the plasma react with the surface metal to form a stable nitride layer, improving corrosion resistance;

[0141] Composite coating technology: After surface densification, a layer of thin film is added to the surface of the composite sheet through composite coating technology to further improve its corrosion resistance and wear resistance. After laser densification and plasma-assisted treatment, a layer of metal film (such as nickel, chromium, etc.) is coated on the surface of the composite sheet through electroplating to improve its wear resistance and corrosion resistance.

[0142] Metal coating thickness formula:

[0143] Where T coating is the coating thickness; I is the current; t is the electroplating time; M is the molar mass of the metal; n is the number of electrons transferred in the electroplating reaction; F is the Faraday constant; ρ is the metal density; A is the electroplating area

[0144] By controlling the current density and time of electroplating, the uniformity and thickness of the metal coating can be ensured, further improving the surface durability of the composite sheet.

[0145] Ceramic composite coating

[0146] A ceramic composite coating (such as aluminum oxide, silicon nitride, etc.) is added to the outer layer of the metal coating to form a composite coating structure, thereby improving the stability of the composite sheet under high temperature and high humidity conditions.

[0147] Ceramic coating densification:

[0148]

[0149] Where: ceramic is the density of the ceramic coating; m is the ceramic mass and V is the volume of the ceramic coating.

[0150] Ceramic composite coating can significantly improve the corrosion resistance and heat resistance of the composite sheet and extend the service life of the composite sheet

[0151] An ultrafine diamond composite sheet, characterized by comprising the following proportions:

[0152] Ultrafine diamond particles: 50% to 70%, particle size: 0.1μm-1μm;

[0153] Cobalt-based alloy powder: 20% ~ 30%;

[0154] Reinforcement material: 5% to 10%;

[0155] Interface binder: 2% to 5%;

[0156] Dispersant: appropriate amount.

[0157] Formula 1 (traditional formula): The surface microhardness is unevenly distributed, the hardness of some local areas drops to 1200 HV, the density is poor, and the corrosion resistance is medium.

[0158] Formula 2 (optimized formula): hardness is evenly distributed, the average surface hardness is 1750HV, the surface finish is significantly improved, the density is good, and the corrosion resistance is excellent.

[0159] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for producing an ultrafine diamond composite sheet, characterized in that: The steps include: S1. Raw material selection and pretreatment: Diamond particles: Select high-purity diamond powder with a particle size of 0.1μm-1μm; Matrix material: Use cemented carbide, such as cobalt-based alloy as the matrix; Reinforcement materials: Add nano-scale ceramic particles, such as silicon nitride and alumina, as reinforcement materials to fill the gaps between the matrix and diamond particles and increase the density of the material; S2. Diamond particles are evenly distributed by combining mechanical stirring with ultrasonic dispersion to fully mix the diamond particles and the matrix powder, wherein mechanical stirring is used to stir the matrix powder and the diamond particles at a low speed to preliminarily disperse the particles, and ultrasonic dispersion is used for 1-2 hours to make the particles more evenly dispersed; S3, high temperature sintering, using high temperature and high pressure sintering technology. The sintering conditions are pressure of 6GPa-8GPa, temperature of 1400℃-1500℃, and sintering time is controlled within 30 minutes. A diffusion model is built in the sintering process. The relationship between sintering temperature, pressure and sintering time is calculated through the diffusion model to obtain the best bonding strength. The diffusion model formula is: Where: D is the diffusion coefficient, D0 is the pre-factor, Q is the activation energy, R is the gas constant, T is the sintering temperature, and by adjusting the temperature T and pressure parameters, which control the diffusion rate of the matrix material and affect the bonding strength between particles; S4, surface densification treatment. After sintering, the surface of the composite sheet is subjected to laser densification treatment. The laser parameters are controlled to have a power density of 10^6-10^7 W / cm 2 The processing time is 3 minutes to 5 minutes.

2. The method for producing an ultrafine diamond composite sheet according to claim 1, characterized in that: In the step S3, high temperature sintering, a graded sintering strategy is also adopted, which includes a three-stage temperature increase strategy, so that the diamond particles and the matrix material can be gradually and stably combined in a gentle temperature gradient; The first stage: the temperature is initially raised to 1400°C and kept at this temperature for 5 minutes. The temperature is lower than the graphitization point, so that the matrix powder particles are slightly fused, the density of the material is improved, and a stable base is provided for subsequent heating. The second stage: further heating to 1450°C, holding time 10 minutes, this stage improves the bonding effect between diamond particles and matrix materials, while controlling the temperature below the critical point of graphitization; The third stage: the temperature is raised to 1500°C and kept at this temperature for 3 minutes to ensure complete sintering of the matrix. At the same time, low temperature and high pressure are used to prevent surface oxidation of the particles and graphitization of the interface.

3. The method for making an ultrafine diamond composite sheet according to claim 2, characterized in that: The graded sintering strategy also includes optimizing the heating path and using a nonlinear heating curve so that the heating rate is faster in the low temperature section and gradually slows down in the high temperature section to reduce the thermal stress between particles; Nonlinear temperature rise formula: Where: T(t) is the temperature at time t, T init is the starting temperature, T final is the target temperature, t total is the total heating time, α is the heating rate control index, and a value greater than 1 can slow down the heating rate in the high temperature section.

4. The method for producing an ultrafine diamond composite sheet according to claim 3, characterized in that: The heating path optimization also includes controlling the heating rate, which includes temperature and diffusion rate control and heating rate adaptive control; The diffusion rate formula is: Where: D is the diffusion coefficient, D0 is the diffusion pre-factor, Q is the activation energy of diffusion, R is the gas constant, and T is the current temperature; The temperature rise rate is adaptively controlled, and the temperature change during the sintering process is fed back in real time through the temperature sensor and the control system, and the temperature rise rate is adjusted in real time using an adaptive control algorithm to maintain the stability of the temperature change; Adaptive control formula: S rate (t+1)=S rate (t)-η(T actual -T target ) Where: S rate (t+1) is the heating rate at the next moment, η is the adjustment coefficient, T actual is the current actual temperature, T target is the target temperature.

5. The method for making an ultrafine diamond composite sheet according to claim 4, characterized in that: The three-stage heating strategy in the graded sintering strategy introduces multiple insulation stages to set insulation intervals at different temperature stages during the heating process to make the heat distribution in the material uniform; Maintain constant temperature at the target temperature point in each stage to allow the matrix and diamond particles to fully diffuse and fuse. Insulation stage formula T hold = constant, maintain constant temperature T during the insulation time hold , ensuring that the material is heated evenly; In graded sintering, the holding time is extended to promote the migration distance of diamond particles to reach the optimal value. The optimal holding time can be determined by calculating the diffusion distance. Diffusion distance formula: Where: L is the diffusion distance, D is the diffusion coefficient, t hold For the holding time, select the appropriate holding time t hold Make the diffusion distance L meet the requirements.

6. The method for making an ultrafine diamond composite sheet according to claim 5, characterized in that: The graded sintering further optimizes the graded sintering atmosphere, utilizes inert gas protection, introduces inert gas into the sintering environment, and ensures the stability of the diamond particles through the protective atmosphere formula; Protective atmosphere control formula: Where: C inert is the inert gas concentration, V inert is the inflow of inert gas, V chamber The volume of the sintering furnace is maintained at a concentration of inert gas above 95% during the high temperature stage.

7. The method for making an ultrafine diamond composite sheet according to claim 6, characterized in that: The atmosphere pressure control is further introduced into the graded sintering atmosphere optimization to dynamically adjust the pressure of the sintering cavity according to different stages in the graded sintering; Atmosphere pressure linkage formula: P inert (t)=P0+α·T(t) Where: P inert (t) is the inert gas pressure, P0 is the initial pressure, T(t) is the temperature at time t, and α is the adjustment parameter.

8. The method for making an ultrafine diamond composite sheet according to claim 1, characterized in that: The step S4, surface densification treatment, uses a multi-step laser scanning process; The multi-step laser scanning process includes: First scan: low-power rapid scan to preliminarily fill tiny pores on the surface; Second scan: Scan slowly with moderate power to further eliminate surface micropores and improve density; The third scan: high-power fine scanning to form a dense and smooth surface layer; Laser power and scanning speed formula: E input =P·t scan Where: E input is the input energy, P is the laser power, t scan is the scan time.

9. The method for producing an ultrafine diamond composite sheet according to claim 8, characterized in that: The step S4, surface densification treatment, includes using argon plasma to pre-treat the surface before densification to remove surface oxides and activate the surface layer, and after laser densification treatment, nitrogen plasma passivation to form a nitride layer on the surface; Plasma activation formula: Where: D plasma is the diffusion coefficient after plasma treatment, E a is the activation energy, k is the Boltzmann constant, and T is the temperature.

10. An ultrafine diamond composite sheet, characterized in that: Including the following ratios: Ultrafine diamond particles: 50% to 70%, particle size: 0.1μm-1μm; Cobalt-based alloy powder: 20% ~ 30%; Reinforcement material: 5% to 10%; Interface binder: 2% to 5%; Dispersant: appropriate amount.

Citation Information

Cited By

  • Low-temperature activated sintering method of solid-waste-based high-temperature heat storage material

    CN122036316A